Enzyme and microbial technology: biotechnology of fats and oils. - Salleh, Abu Bakar; Abd. Razak, Che Nyonya; Wan Yunus, Wan Md. Zin; Ampon, Kamaruzaman; Basri, Mahiran (1991)
To develop an enzyme technology industry, a sizeable enzyme bank is a priority requirement. A group of enzymes of interest to us and currently attracting attention of researchers throughout the world are the lipases. Apart from their usual hydrolytic properties, these enzymes can perform synthetic reactions under controlled conditions. Our group have meticulously carried out a screening programme for microbes that can produce these enzymes. So far we have isolated over 50 microbial isolates exhibiting lipolytic activities on plate and managed to study in detail 3 fungi and 2 bacteria. To improve the versatility of these enzymes we are redesigning the enzymes with the hope of obtaining an analogue with better solubility in organic solvents. We have covalently attached aldehydes of various sizes and hydrophobicity onto the enzyme lipase, and the enzyme thus derivatised showed. enhanced catalytic activity and thermal stability compared with the native unmodified enzyme. Another approach is to immobilise the enzyme. The enzyme molecule is still, in principle, to another molecule. In most cases, the molecule attached yo the enzyme is usually insoluble, hence confering the derivatised enzyme a new property of insolubility. We have shown that enzymes can be immobilised by simple adsorption onto readily available resins.